TAFSIR SEMANTIK TERHADAP SURAT AL-KAFIRUN - Muslimin, Imam (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
The problems about the reading of al-Qur’an is always interesting to be discussed, in which the use of Arabic includes sound or ‘nash’ is acrucial factor to understand the implicit meaning of the Arabic-written texts. Al-Qur’an discusses problem based on the society’s culture. Al-Kafirun discusses not only about the normative theology but more about sociological contexts in which it tends to show transparency, fight against fanaticism and regionalism. And all of the will bring to the first process of the making of the text meaning to the situational context that creates them.